A ascensão de regimes autoritários nas primeiras décadas do século XXI: reflexões e enfrentamentos a partir d’a filosofia das formas simbólicas e do mito do estado de Ernst Cassirer - Jesus, Edilson Belangier de (2024)
The main objective of this work is to analyze the rise of authoritarian regimes in the 21st century through the philosophy of Ernst Cassirer (187431945), a topic relevant to both society and the scientific community. This investigation focuses on how these regimes employ symbolic and mythological strategies to consolidate power, thereby undermining democratic principles. Using Ernst Cassirer9s theoretical paradigm, especially his works on the *Philosophy of Symbolic Forms* and *The Myth of the State*, the research seeks to understand the symbolic mechanisms that facilitate the emergence of such regimes and offers reflections on how to confront them. Adopting a qualitative approach, the research is based on bibliographic and documentary analysis of Cassirer9s works, in dialogue with other contemporary philosophers. It includes a critical review of existing literature on the use of symbols and myths in politics, with a special focus on media manipulation and the spread of fake news. The methodology incorporates a study of case examples of recent authoritarian regimes, juxtaposing these empirical materials with Cassirer9s theoretical conceptions to identify patterns and similar strategies. Modern authoritarian regimes utilize digital technologies and symbolic manipulation techniques to shape public opinion and consolidate power. The research identified media and fake news as secondary factors in establishing political myths that support and sustain these regimes, highlighting the urgent need for critical education to raise awareness of the uses of symbols and myths in politics. In Cassirer9s philosophy, valuable insights can be found for understanding and combating the rise of authoritarian regimes, with critical education4specifically the ability to engage with symbolic forms4being indispensable to resisting authoritarian manipulation. Cassirer argues that the development of new narratives and symbols can encourage resistance to authoritarianism and contribute to the construction of a fairer and more democratic society. The study aims to advance understanding of the symbolic dynamics in contemporary politics and suggest avenues for future research on combating authoritarianism through education and the creation of new symbolic forms